2014
DOI: 10.1038/nbt.3063
|View full text |Cite
|
Sign up to set email alerts
|

Functional optimization of gene clusters by combinatorial design and assembly

Abstract: Large microbial gene clusters encode useful functions, including energy utilization and natural product biosynthesis, but genetic manipulation of such systems is slow, difficult and complicated by complex regulation. We exploit the modularity of a refactored Klebsiella oxytoca nitrogen fixation (nif) gene cluster (16 genes, 103 parts) to build genetic permutations that could not be achieved by starting from the wild-type cluster. Constraint-based combinatorial design and DNA assembly are used to build librarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
329
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(332 citation statements)
references
References 52 publications
2
329
0
1
Order By: Relevance
“…Many of these software tools can also control liquid handling robots and their ability to automate hundreds of complex modular assemblies has been recently demonstrated 62 . Not surprisingly, companies have emerged from these efforts that now sell advanced DNA assembly software to clients.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these software tools can also control liquid handling robots and their ability to automate hundreds of complex modular assemblies has been recently demonstrated 62 . Not surprisingly, companies have emerged from these efforts that now sell advanced DNA assembly software to clients.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Implementing standards for large DNA assembly projects is also beginning to bear fruit. By using a variation of the MoClo Golden Gate standard, researchers were recently able to automate the design and construction of 122 different versions of a cluster of 16 genes for nitrogen fixation, building from a starting library of 103 parts 62 . At the largest scale of DNA assembly, the landmark genome synthesis projects for Mycoplasma genitalium 63 and Mycoplasma mycoides 64 have shown that different scales of assembly require different methods: Gibson assembly can be used to join gene-size DNA fragments in a scale of up to a hundred kilobases, but beyond that in vivo recombination assembly in S. cerevisiae becomes necessary.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Given that biosynthesis pathways often consist of multiple enzymatic cascades to generate the final products, rational engineering of all the enzymes involved in the pathway may not be the most efficient strategy for non-natural product biosynthesis. Therefore, alternative methods such as directed evolution 42 , mutagenesis 25,43 , pathway recombination 30,44 or semi-synthesis 6,45,46 strategies for generating natural product analogues should be systematically explored in greater detail.…”
Section: Purification Of 7-chloro Analogues Of Violacein and Deoxyviomentioning
confidence: 99%
“…Mais deux difficultés principales émergent : la conception de la régulation nécessaire au fonctionnement d'un tel programme ADN et son exécution initiale par des machines moléculaires. Faire fonctionner in vivo des circuits génétiques élémentaires synthétiques construits en laboratoire, même s'ils sont composés de séquences codantes bien caractérisées, est encore aujourd'hui un obstacle sérieux, quand bien même des progrès ont été réalisés récemment [41]. Le problème réside aussi dans le couplage de l'information digitale portée par l'ADN et de la dynamique des processus liés à l'autoreproduction qui sont essentiellement analogiques.…”
Section: Le Métabolismeunclassified